Plasmodium falciparum multidrug resistance protein 1 and artemisinin-based combination therapy in Africa - Dahlstrom, Sabina (2018)
Plasmodium falciparum response mechanisms to the major artemisinin-based combination therapies (ACTs) are largely unknown. Multidrug-resistance protein (MRP)-like adenosine triphosphate (ATP)-binding cassette transporters are known to be related to multidrug resistance in many organisms. Therefore, we hypothesized that sequence variation in pfmrp1 can contribute to decreased parasite sensitivity to ACT. Through sequencing of the pfmrp1 open reading frame for 103 geographically diverse P. falciparum infections, we identified 27 single-nucleotide polymorphisms (SNPs), of which 21 were nonsynonymous and 6 synonymous. Analyses of clinical efficacy trials with artesunate-amodiaquine and artemether-lumefantrine detected a specific selection of the globally prevalent I876V SNP in recurrent infections after artemether-lumefantrine treatment. Additional in silico studies suggested an influence of variation in amino acid 876 on the ATP hydrolysis cycle of pfMRP1 with potential impact on protein functionality. Our data suggest for the first time, to our knowledge, the involvement of pfMRP1 in P. falciparum in vivo response to ACT.